An allelopathic competition model with quorum sensing and delayed toxicant production - Paolo Fergola; Marianna Cerasuolo; Edoardo Beretta (Mathematical Biosciences and Engineering)
The dynamics of a differential functional equation system representing an allelopathic competition is analyzed. The delayed allelochemical production process is represented by means of a distributed delay term in a linear quorum-sensing model. Sufficient conditions for local asymptotic stability properties of biologically meaningful steady-state solutions are given in terms of the parameters of the system. A global asymptotic stability result is also proved by constructing a suitable Lyapunov functional. Some simulations confirm the analytical results.